CavatermTM plus treatment in high - risk surgical patients - Zinatossadat Bouzari; Ebrahim Alijanpour; shahla yazdani; Azita Ghanbarpour; Ali Bijani; Tahereh Ashraf Ganjoei; hemmat gholinia (Babol University of Medical Sciences, 2021)
Background: The purpose of the study was to evaluate the effectiveness and safety of thermal balloon ablation in women with high anesthetic and surgical risk compared to invulnerable women according to the American Society of Anesthesia (ASA) physical status stratification. Methods: This report was based on a retrospective cohort study of women with heavy menstrual bleeding (HMB) who were eligible for treatment with CavatermTM plus during 2012-2017. Women were classified as high-risk (HR) or low-risk (LR) cohorts based on ASA physical status stratification. The primary outcome includes amenorrhea in the twelfth months after the treatment. Risk adjustments were performed using regression models. Results: This research study consisted of 63 women with mean age 44.42±5.48. Mean of body mass index (BMI) in the HR cohort was higher than the LR cohort (31.48±6.22 vs 26.83± 3.51, P=0.005) and results were also similar considering the uterine length (mm) between HR and LR women (58.27±35.70 vs 30.92± 35.30, P=0.01). The primary outcome of treatment after a one-year follow-up in the two groups (HR and LR) was 31 (93.9%) and 15 (78.9%), respectively. After adjusting for known confounders including age, uterine length, parity, dysmenorrheal, the adjusted odds ratio was 0.94 (95% CI, 0.14- 2.5; P= 0.60). Conclusion: For women with high anesthetic and surgical risks derived from serious underlying co morbidities, endometrial ablation can provide a minimally invasive, safe, and effective therapy for heavy menstrual bleeding.